PARADIGMA "EDUCATION FOR ALL" DALAM PRAKTEK PEMBELAJARAN INKLUSI DI SEKOLAH DASAR - Endang Poerwanti (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2013)
Abstract: "Education for all" paradigm in inclusion teaching practices at elementary school in Malang city. Inclusive education involved special needs’ students to learn together with normal children in regular schools. In field condition, teachers in regular schools are not prepared to teach special needs’ students. The purpose of this fundamental research was to develop basic concepts about the teacher behavior related to inclusion education in handling special needs’ students and their behavior problems in the classroom. The research was conducted at five elementary schools in Malang. Interview, observation, documentation and FGD were used data collection methods. Results showed: (1) teachers had been working independently to develop their knowledge and skill in coping with special needs’ students, (2) sustainable guidance should be conducted, (3) stakeholder support should be improved, (4) there were some schools had not adequate facilities and therapy rooms. Abstrak: Paradigma "education for all" dalam praktik pembelajaran inklusi di sekolah dasar kota Malang. Pendidikan Inklusi mengikutsertakan Anak Berkebutuhan Khusus (ABK) belajar bersama anak normal di sekolah reguler. Kondisi di lapangan, guru di sekolah reguler tidak dididik secara khusus untuk menghadapi ABK. Penelitian fundamental ini bertujuan menyusun konsep dasar tentang perilaku guru berwawasan pendidikan inklusi dalam penanganan ABK dan perilaku bermasalah di kelas. Penelitian dilaksanakan di lima SD di kota Malang. Observasi, wawancara, dokumentasi, dan FGD digunakan sebagai metode pengumpulan data. Hasil penelitian menunjukkan (1) guru secara mandiri telah berupaya mengembangkan pengetahuan dan keterampilan menangani ABK, (2) pembinaan secara berkelanjutan sangat diperlukan, (3) perlu peningkatan dukungan stakeholder, (4) beberapa sekolah belum memiliki sarana dan ruang terapi yang memadai. Kata Kunci: pendidikan Insklusi, sekolah dasar